A New Role for Helicobacter pylori Urease: Contributions to Angiogenesis - Olivera-Severo, Deiber; Uberti, Augusto F.; Marques, Miguel S.; Pinto, Marta T.; Gomez-Lazaro, Maria; Figueiredo, Céu; Leite, Marina; Carlini, Célia R. (Frontiers in Microbiology, 2017)
Helicobacter pylori is a pathogen involved in gastric diseases such as ulcers and carcinomas. H. pylori’s urease is an important virulence factor produced in large amounts by this bacterium. In previous studies, we have shown that this protein is able to activate several cell types like neutrophils, monocytes, platelets, endothelial cells and gastric epithelial cells. Angiogenesis is a physiological process implicated in growth, invasion and metastization of tumors. Here we have analyzed the angiogenic potential of H. pylori urease (HPU) in gastric epithelial cells. No cytotoxicity was observed in AGS, Kato-III, and MKN28 gastric cell lines treated with 300 nM HPU, as evaluated by the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. As we previously reported in neutrophils, treatment with 300 nM HPU also had an anti-apoptotic effect in gastric epithelial cells leading to a 2.2-fold increase in the levels of Bcl-XL after 6 h, and a decrease of 80 % in the content of BAD, after 48 h, two mitochondrial proteins involved in regulation of apoptosis. Within 10 min of exposure, HPU is rapidly internalized by gastric epithelial cells. Treatment of the gastric cells with methyl–cyclodextrin abolished HPU internalization suggesting a cholesterol-dependent process. HPU induces the expression of pro-angiogenic factors and the decrease of expression of anti-angiogenic factors by AGS cells. The angiogenic activity of HPU was analyzed using in vitro and in vivo models. HPU induced formation of tube-like structures by human umbilical vascular endothelial cells (HUVECs) in a 9 h experiment. In the chicken embryo chorioallantoic membrane model (CAM), HPU induced intense neo-vascularization after 3 days. In conclusion, our results indicate that besides allowing bacterial colonization of the gastric mucosa, H. pylori’s urease triggers processes that initiate pro-angiogenic responses in different cellular models. Thus, this bacterial urease, a major virulence factor, may also play a role in gastric carcinoma development.